2013
DOI: 10.1007/s00701-013-1633-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of endovascular treatment of brain arteriovenous malformation using Onyx in a series of 92 consecutive patients

Abstract: Embolization of brain AVM using Onyx and detachable tip microcatheters results in a relatively high rate of complete obliteration. Angioarchitecture of the lesion can predict treatment success. Higher amounts of Onyx injected per session increase the bleeding risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…The recent work of Bervini and colleagues, Nerva and colleagues, as well as the report in the current issue provide sufficient substance to recommend microsurgery to patients with unruptured AVM Spetzler-Martin grade 1 and 2 (corresponding to Spetzler-Ponce class A) [3,11,14,16]. In contrast, treatment of unruptured Spetzler-Martin grade 3 and 4 AVMs needs to be seen critically.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The recent work of Bervini and colleagues, Nerva and colleagues, as well as the report in the current issue provide sufficient substance to recommend microsurgery to patients with unruptured AVM Spetzler-Martin grade 1 and 2 (corresponding to Spetzler-Ponce class A) [3,11,14,16]. In contrast, treatment of unruptured Spetzler-Martin grade 3 and 4 AVMs needs to be seen critically.…”
mentioning
confidence: 81%
“…It was soon realized, however, that complete elimination could not be routinely achieved. The introduction of Onyx, offering more controllable intranidal dispersion, did not change the picture fundamentally, achieving complete elimination in maximally 50 % [5,13,16]. Embolization also remained associated with substantial complications despite technical advances.…”
mentioning
confidence: 99%
“…54 Strauss et al also found that large pedicles (defined as twice the normal diameter) had an odds ratio of 4.6 of complete obliteration compared with small pedicles. 60 Feeding artery location is likewise associated with complete obliteration, with superficial arteries positively associated with cure 60 while feeders arising from lenticulostriate and thalamoperforating arteries were associated with an inability to achieve complete occlusion. 69 Importantly, the presence of en passage arteries was found to be negatively associated with complete embolization.…”
Section: Feeding Arteriesmentioning
confidence: 95%
“…30 Other studies adopt a general approach of attempting endovascular cure with all or most AVMs without stating specific guiding principles and then refer the failures for surgery or radiosurgery. 26,60,69 Still other studies report broad guidelines used to select AVMs for curative embolization but do not specifically report outcomes for that subset. 38,53 In general, these studies confirm that complete occlusion using embolization is possible and they begin to define the AVM characteristics most predictive of endovascular cure.…”
Section: Endovascular Embolization In Avm Managementmentioning
confidence: 96%
“…In another series of 82 patients by Panagiotopoulos et al, 20 AVMs (24.4%) were completely embolized with Onyx (13). Strauss et al in their series of 92 cases reported a 27% cure rate and concluded that complete obliteration rates were significantly higher in lesions with superficial big feeding arteries (14). According to the published experience up to now, complete obliteration rates of AVMs with Onyx range obviously above the reported average of 10% of angiographic cure after embolization with n-BCA (15).…”
Section: Discussionmentioning
confidence: 96%